NILAI RELIGIUS KITAB SIWA RATRI KALPA KARYA EMPU TANAKUNG (SEBUAH KAJIAN SOSIOLOGI SASTRA) - I Nyoman Reteq; Paulina Maria Yovita Kosat; Jeladu Kosmas; Dian Sari A. Pekuwali; Liski A.Th. Subu Taopan (Jurnal Lazuardi, 2023)
The problem in this research is what religious values ​​are implied in the book Siwaratri Kalpa by Empu Tanakung. The aim of the research is to describe what religious values ​​are implied in the book Siwaratri Kalpa by Empu Tanakung. The method used in this research is descriptive qualitative method. This method is used because this research uses descriptive data by explaining, examining, or describing something that already exists. The data in this study are in the form of words, sentences or paragraphs which are indicated to have sociological values ​​contained in the book Siwaratri Kalpa by Empu Tanakung. In collecting data, the writer uses library techniques, namely by analyzing the contents. In this analysis, the researcher listens and then records documents taken from primary data relating to the problem and research objectives. The data is in the form of novel data, so the research tries to examine the contents of the novel. The results of the research show that the religious value implied in Lubdaka as a kalua hunter is connected with the modern situation of today's modern society, it turns out that there are still many human beings who prefer to hunt for physical satisfaction, so he will tend to be more concerned with material things, as if they were the most essential prestige in this world. He would not feel that matter would actually be able to lead people into the abyss of sin if humans could not control it. Then humans who have fallen into the valley of sin will always feel far from God Almighty. If humans already feel far from God then it will be as if they have forgotten the essence of humanity. If man is far from his Creator, it means that he has forgotten his human essence. Kata Kunci: Religious Values, Siwa Ratri Kalpa, Sociology of Literature